2017
DOI: 10.1007/s00223-017-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Markers of Inflammation and Muscle Mass, Strength and Function: Findings from the Hertfordshire Cohort Study

Abstract: We investigated the longitudinal relationships between inflammation markers and the following outcomes in a UK cohort study: appendicular lean mass (ALM); walking speed; level and change in grip strength; and sarcopenia defined by the European Working Group on Sarcopenia in Older People. Analyses were based on 336 community-dwelling older men and women (aged 59–70 years) who participated in the Hertfordshire Cohort Study (HCS). Inflammation markers were ascertained at baseline using enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
(33 reference statements)
4
35
2
2
Order By: Relevance
“…Not only exist those advantages of HI-RT but also are there several disadvantages of HV-RT, eg, the longer time of recovery 72 along with an increased risk of overtraining and a greater inflammatory response 72 which itself is considered one factor in the genesis of sarcopenia. 73,74 Additionally, high levels of heart rate and systolic blood pressure have been observed in HV-RT sets, 75 another factor that plays a role for sarcopenic patients, which often demonstrate cardiovascular comorbidities. 76 To the best of our knowledge, our study is the first to evaluate the effects of HI-RT in combination with dietary supplementation on sarcopenic community-dwelling men of such advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…Not only exist those advantages of HI-RT but also are there several disadvantages of HV-RT, eg, the longer time of recovery 72 along with an increased risk of overtraining and a greater inflammatory response 72 which itself is considered one factor in the genesis of sarcopenia. 73,74 Additionally, high levels of heart rate and systolic blood pressure have been observed in HV-RT sets, 75 another factor that plays a role for sarcopenic patients, which often demonstrate cardiovascular comorbidities. 76 To the best of our knowledge, our study is the first to evaluate the effects of HI-RT in combination with dietary supplementation on sarcopenic community-dwelling men of such advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…First, the relationship between loss of muscle mass and strength may be bidirectional. Reductions in strength may result in declines in physical function and activity, leading to disuseinduced muscle wasting; simultaneously, declines in muscle mass and quality due to losses in fast-twitch muscle fibres, fat infiltration of skeletal muscle and increased inflammation may result in declines in strength and physical function [50]. Second, correlations between muscle mass and strength and BMD in older age are expected from both cellular and physiological perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were identified by Pin et al, who also found significant associations between muscle catabolism and interleukin 6 level [ 35 ]. Furthermore, Westbury et al showed significant relationships between C-reactive protein and lower grip strength [ 36 ]. Additionally, a higher interleukin 8 level was associated with an increased risk of sarcopenia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%